The Immune-microenvironment Confers Chemoresistance of Colorectal Cancer through Macrophage-Derived IL6 - Yin, Yuan; Yao, Surui; Hu, Yaling; Feng, Yuyang; Li, Min; Bian, Zehua; Zhang, Jiwei; Qin, Yan; Qi, Xiaowei; Zhou, Leyuan; Fei, Bojian; Zou, Jian; et al. (Clinical cancer research, 2017)
Tumor-associated macrophages (TAMs) are frequently associated with poor prognosis in human cancers. However, the effects of TAMs in colorectal cancer are contradictory. We therefore investigated the functions, mechanisms, and clinical significance of TAMs in colorectal cancer. We measured the macrophage infiltration (CD68), P-gp, and Bcl2 expression in colorectal cancer tissues using IHC staining. Coculture of TAMs and colorectal cancer cells both and models was used to evaluate the effects of TAMs on colorectal cancer chemoresistance. Cytokine antibody arrays, ELISA, neutralizing antibody, and luciferase reporter assay were performed to uncover the underlying mechanism. TAM infiltration was associated with chemoresistance in patients with colorectal cancer. Colorectal cancer-conditioned macrophages increased colorectal cancer chemoresistance and reduced drug-induced apoptosis by secreting IL6, which could be blocked by a neutralizing anti-IL6 antibody. Macrophage-derived IL6 activated the IL6R/STAT3 pathway in colorectal cancer cells, and activated STAT3 transcriptionally inhibited the tumor suppressor miR-204-5p. Rescue experiment confirmed that miR-204-5p is a functional target mediating the TAM-induced colorectal cancer chemoresistance. miR-155-5p, a key miRNA regulating C/EBPβ, was frequently downregulated in TAMs, resulting in increased C/EBPβ expression. C/EBPβ transcriptionally activated IL6 in TAMs, and TAM-secreted IL6 then induced chemoresistance by activating the IL6R/STAT3/miR-204-5p pathway in colorectal cancer cells. Our data indicate that the maladjusted miR-155-5p/C/EBPβ/IL6 signaling in TAMs could induce chemoresistance in colorectal cancer cells by regulating the IL6R/STAT3/miR-204-5p axis, revealing a new cross-talk between immune cells and tumor cells in colorectal cancer microenvironment. .